Scoping review protocol: auriculotherapy in children and adolescents in the context of Health Care (Research, Society and Development, 2021)
The objective of this study is to map and analyze the scientific production about auriculotherapy for children and adolescents in the context of health care. For that, the PCC strategy was used: (P) Participants – Children and Adolescents between 6 and 12 years old (WHO); (C) concept: auriculotherapy; and (C) Context: comprehensive health care, as recommended by scholars (Aromataris & Munn, 2020). Which gave rise to the following question: What is the evidence in the scientific literature on auriculotherapy for children and adolescents in the context of comprehensive health care? This scope review will consider original studies, carried out exclusively with human beings, children aged between 6 and 12 years old, published in full in national and international journals, free or not, with a qualitative and/or quantitative approach, in Portuguese, English and Spanish. Studies should address the use of auriculotherapy in health care. Thus, studies with variations in auriculotherapy resources (vaccaria seeds, magnetic spheres and crystals) will be considered. The indexed sources that will be used for the scope review are: Online Medical Literature Analysis and Retrieval System (MEDLINE); Latin American and Caribbean Literature on Health Sciences (LILACS); Scientific Electronic Library online (SCIELO); the Cochrane Database of Systematic Reviews (CDCR), the Brazilian Dentistry Bibliography (BBO), as well as the Virtual Health Library in Traditional, Complementary and Integrative Medicines (BVS MTCI), Adolescent Health Virtual Library (ADOLEC) and Physiotherapy Evidence Database (PEDro). To search the gray literature, the Coordination for the Improvement of Higher Education Personnel (CAPES) will be consulted. Searches in these indexed sources will be carried out between february and march 2022. It is expected that this review will contribute to the state of the art regarding the production and implementation of Complementary Integrative Practices in Health (PICS).